Genomic Insights Into the Demographic History of the Southern Chinese - Huang, Xiufeng; Xia, Zi-Yang; Bin, Xiaoyun; He, Guanglin; Guo, Jianxin; Adnan, Atif; Yin, Lianfei; Huang, Youyi; Zhao, Jing; Yang, Yidong; Ma, Fuwei; Li, Yingxiang; et al. (Frontiers in Ecology and Evolution, 2022)
Southern China is the birthplace of rice-cultivating agriculture and different language families, and has also witnessed various human migrations that facilitated cultural diffusions. The fine-scale demographic history in situ that forms present-day local populations, however, remains unclear. To comprehensively cover the genetic diversity in East and Southeast Asia, we generated genome-wide SNP data from 211 present-day Southern Chinese and co-analyzed them with ~1,200 ancient and modern genomes. In Southern China, language classification is significantly associated with genetic variation but with different extent of predictability, and there is strong evidence for recent shared genetic history particularly in Hmong-Mien and Austronesian speakers. A geography-related genetic sub-structure that represents the major genetic variation in Southern East Asians is established pre-Holocene and its extremes are represented by Neolithic Fujianese and First Farmers in Mainland Southeast Asia. This sub-structure is largely reduced by admixture in ancient Southern Chinese since > ~2,000 BP, which forms a ‘Southern Chinese Cluster’ with a high level of genetic homogeneity. Further admixture characterizes the demographic history of the majority of Hmong-Mien speakers and some Kra-Dai speakers in Southwest China happened ~1,500 – 1,000 BP, coeval to the reigns of local chiefdoms. In Yellow River Basin, we identify a connection of local populations to genetic sub-structure in Southern China with geographical correspondence appearing > ~9,000 BP, while the gene flow likely closely related to ‘Southern Chinese Cluster’ since the Longshan period (~5,000 – 4,000 BP) forms ancestry profile of Han Chinese Cline. Finally, in the border between China and Mainland Southeast Asia, we document two admixture events related to the formation of present-day Tibeto-Burman, Kra-Dai, and Vietic speakers in this region.